Diversity of Dragonfly in The Segenter Waterfall Ecotourism Area, Lombok Island - Ilhamdi, Mohammad Liwa; Al Idrus, Agil; Zulkifli, Lalu; Santoso, Didik; Mertha, I Gde; Alhafizin, M.; Madang, Kodri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Dragonflies are a part of biodiversity that possess aesthetic value due to their colorful appearance, as well as ecological, environmental, ecotourism, and educational significance. Segenter Waterfall in West Lombok has a unique bio-ecological characteristic, as it provides a habitat for various interesting dragonfly species. This can be utilized as an object for ecotourism and a learning resource. The aim of this research was to analyze the diversity of dragonflies in Segenter Waterfall. The method used in this research was a survey method with an area exploration technique following predetermined transect lines based on observation results: the edge path, the middle path, and the watershed path. The sweeping net method was used to collect dragonflies that could not be identified in the field for further observation in the laboratory. The results showed that the highest species abundance was Orthetrum sabina (0.55) and the lowest was Anax guttatus (0.19). Meanwhile, the highest diversity index was found in the water path (2.96) and the lowest in the middle path (2.74). In conclusion, the diversity of dragonfly species varies across each observation path, with the highest order being the Water Path, followed by the Edge Path, and the lowest being the Middle Path in the Segenter Waterfall area, Lombok Island.